Using Instructional Design, Analyze, Design, Develop, Implement, and Evaluate, to Develop e-Learning Modules to Disseminate Supported Employment for Community Behavioral Health Treatment Programs in New York State - Patel, Sapana R.; Margolies, Paul J.; Covell, Nancy H.; Lipscomb, Cristine; Dixon, Lisa B. (Frontiers in Public Health, 2018)
Background Implementation science lacks a systematic approach to the development of learning strategies for online training in evidence-based practices (EBPs) that takes the context of real-world practice into account. The field of instructional design offers ecologically valid and systematic processes to develop learning strategies for workforce development and performance support. Objective This report describes the application of an instructional design framework—Analyze, Design, Develop, Implement, and Evaluate (ADDIE) model—in the development and evaluation of e-learning modules as one strategy among a multifaceted approach to the implementation of individual placement and support (IPS), a model of supported employment for community behavioral health treatment programs, in New York State. Methods We applied quantitative and qualitative methods to develop and evaluate three IPS e-learning modules. Throughout the ADDIE process, we conducted formative and summative evaluations and identified determinants of implementation using the Consolidated Framework for Implementation Research (CFIR). Formative evaluations consisted of qualitative feedback received from recipients and providers during early pilot work. The summative evaluation consisted of levels 1 and 2 (reaction to the training, self-reported knowledge, and practice change) quantitative and qualitative data and was guided by the Kirkpatrick model for training evaluation. Results Formative evaluation with key stakeholders identified a range of learning needs that informed the development of a pilot training program in IPS. Feedback on this pilot training program informed the design document of three e-learning modules on IPS: Introduction to IPS, IPS Job development, and Using the IPS Employment Resource Book. Each module was developed iteratively and provided an assessment of learning needs that informed successive modules. All modules were disseminated and evaluated through a learning management system. Summative evaluation revealed that learners rated the modules positively, and self-report of knowledge acquisition was high (mean range: 4.4–4.6 out of 5). About half of learners indicated that they would change their practice after watching the modules (range: 48–51%). All learners who completed the level 1 evaluation demonstrated 80% or better mastery of knowledge on the level 2 evaluation embedded in each module. The CFIR was used to identify implementation barriers and facilitators among the evaluation data which facilitated planning for subsequent implementation support activities in the IPS initiative. Conclusion Instructional design approaches such as ADDIE may offer implementation scientists and practitioners a flexible and systematic approach for the development of e-learning modules as a single component or one strategy in a multifaceted approach for training in EBPs.